How and why I fell into neuropathology - Hauw, Jean-Jacques (Free Neuropathology, 2023)
I'm going to explain how and why I fell into the Department of Neuropathology at the Pitié-Salpêtrière Hospital of Paris. I'd also like to sketch the history of French neuropathology in the years 1960-2010, as seen by a naive young student, and then by a practicing neuropathologist (often still very naive). As a matter of fact, although the history of neurosciences [1-2] and the Pitié-Salpêtrière Hospital in Paris [3-4] have been the subject of numerous publications, the history of neuropathology in this hospital has been rarely documented [5-6]. I spent more than forty years strolling along the alleys of La Salpêtrière, among its old pavilions, the Saint Louis chapel, the “Pavillon des folles,” the courtyard of Manon Lescaut and the guard room. I worked full-time between the Escourolle laboratory, the “Amphithéâtre des morts” and the University. It has been a real pleasure to be part of this world. I would also like to offer young doctors in training and future neuropathologists some advice that might help them in the choice and development of their future careers.